Lithium Titanate (LTO) Synthesis Through Solid State Reaction and Its Performance for LiFePO4/LTO Battery - Viona Natalia; Anggia Putri Gustami; Fitria Rahmawati; Witri Wahyu Lestari; Agus Purwanto (Institute for Research and Community Services (LPPM) ITB, 2018)
Lithium titanate, LTO, was synthesized by solid state reaction with Li2CO3 and TiO2 powder as precursors. The result was characterized to investigate its crystal structure, phase content, cell parameters, surface morphology, electrical conductivity and its performance as electrode in a lithium ion battery. XRD analysis with Le Bail refinement showed that the prepared materials consisted of 4 phases of Li4Ti5O12, Li2TiO3, anatase TiO2 and rutile TiO2. The surface morphology was still not homogeneous, with an average grain size of 0.533 ± 0.157 µm. When 1% LTO was mixed with graphite and used as anode of an LFP battery, it produced a specific capacity of 130.66 mAhg